Approaches and Methods of Optimazing Long-Term Strategy of Pulling Projects of Nuclear Legacy out of Operation - D. F. Ilyasov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies a new approach to shaping possible variants of long-term strategies of pulling projects of nuclear legacy out of operation, which is based on optimization with criteria on min costs and restrictions on resources, radioactive risks and duration of the implementation period. The author put forward different variants of criteria and restrictions of strategy of pulling projects of nuclear legacy out of operation. Methods of resolving the task of optimization were studied that are based on principles of dynamic programming and an example of getting a solution was demonstrated. Benefits and drawbacks of the approach were discussed in comparison with accepted in global and Russian practice methods of prioritization of the procedure of pulling projects out of operation. The article analyzed prospects of using the proposed approach for the development of long-term road map aimed at settling problems of nuclear legacy in the Russian Federation.